Hepatoprotective effect of calyces extract of Physalis peruviana in hepatotoxicity induced by CCl4 in wistar rats - TORO ARANGO, Reina Marcela; ARAGÓN N., Diana Marcela; OSPINA G., Luis Fernando (Vitae, 2013)
Background: Physalis peruviana (“uchuva”, Solanaceae) is a widespread species of the South American Andes and widely used in traditional medicine. Its fruits are consumed as food and for the treatment of diabetes. The juice of Physalis peruviana fruits is topically applied in the eyes for pterigyum treatment. Previous works reported that the fruit extracts has modulating activity of oxidative stress in experimental diabetes models induced by streptozotocin. It has been attributed antipyretic, antimicrobial, analgesic and anti-inflammatory properties to the calyces enveloping the fruit. Reported literature demonstrates in vivo and in vitro that different calyx’s extracts have antioxidant and anti-inflammatory activities. Objectives: To evaluate the in vivo hepatoprotective effect of the extract of Physalis peruviana calyces, involving inflammation and oxidative stress models at hepatic level. Methods: Hepatotoxicity was induced by single oral administration of CCl4 (2 mL / Kg in olive oil) in Wistar rats. Physalis peruviana extract (250 mg/Kg) and silymarin (200 mg/Kg), used as control drug, were administrated twice a day for five days. At the end of the experiment, animals were euthanized and the liver enzymes alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase were measured as well as some parameters of hepatic antioxidant status like superoxide dismutase and catalase activities, protein oxidation and lipid peroxidation. Results: Extract of Physalis peruviana calyces inhibited significantly (p < 0.001) liver oxidative stress caused by CCl4, maintaining superoxide dismutase and catalase activities close to normal. Studied extract also reduced significantly liver enzymes levels increased by CCl4 administration. Conclusion: It was suggested that the extract of Physalis peruviana calyces presents a hepatoprotective effect related to its antioxidant activity, especially regarding to lipid peroxidation inhibition.